Test of a new tip material for Langmuir probe diagnostic - Naz, M.Y. (Maik Nauka-Interperiodica Publishing, 2016)
The objective of the work is to test a nickelâchrome alloy as a probe tip material for characterization of discharge plasmas. In order to meet the objective, a symmetric triple Langmuir probe diagnostic system and an associated driving circuit are designed and tested in an inductively coupled plasma generated by a 13.56-MHz radio frequency source coupled with an automated impedance match network. This probe is used to measure the electron temperature, electron number density, and ion saturation current as functions of the input power of the radio frequency source and the filling gas pressure. An increasing trend is noticed in the electron temperature and electron number density with an increase in the input power, whilst a decreasing trend is evident in these parameters with an increase in the nitrogen gas pressure. The overall inaccuracies in electron temperature and electron number density measurements are 5â12 and 3â13, respectively. Â© 2016, Pleiades Publishing, Ltd.